Trajectories of personal control in cancer patients receiving psychological care. Issue 5 (23rd September 2014) - Zhu, Lei; Schroevers, Maya J.; van der Lee, Marije; Garssen, Bert; Stewart, Roy E.; Sanderman, Robbert; Ranchor, Adelita V.
Abstract Objective This study aimed to (1) identify subgroups of cancer patients with distinct personal control trajectories during psychological care, (2) examine whether socio‐demographic, clinical, and psychological care characteristics could distinguish trajectories, and (3) examine differential patterns of psychological symptoms between trajectories. Methods This naturalistic study focused on 241 cancer patients receiving psychological care at psycho‐oncology institutions. Data were collected before the initiation of psychological care, and 3 and 9 months thereafter. Latent class growth analysis was applied to identify personal control trajectories. Results Three personal control trajectories were identified: enduring improvement (41%), temporary improvement (50%), and deterioration (9%). Education and baseline physical symptoms distinguished these trajectories. In the whole group, improvements in personal control were associated with improvements in psychological symptoms. Patients at distinct trajectories reported different levels of psychological symptoms, but did not differ in their courses of psychological symptoms. Patients in the enduring and temporary control improvement groups experienced significant psychological symptoms reductions over time, whereas patients in the control deterioration group maintained high psychological symptoms. Conclusions Improvements in personal control seem to depend on initial control level: those who start with the highest control levels show subsequent improvements, whereas those with the lowest control levels show subsequent deterioration. Copyright © 2014 John Wiley & Sons, Ltd.